Stratum Corneum Structure and Function Studied by X-ray Diffraction - Hatta, Ichiro (Dermato, 2022)
X-ray diffraction is one of the powerful tools in the study of a variety of structures in the stratum corneum at the molecular level. Resolving structural modifications during functioning is an important subject for clarifying the mechanism of operating principles in the function. Here, the X-ray diffraction experimental techniques used in the structural study on the stratum corneum are widely and deeply reviewed from a perspective fundamental to the application. Three typical topics obtained from the X-ray diffraction experiments are introduced. The first subject is concerned with the disruption and the recovery of the intercellular lipid structure in the stratum corneum. The second subject is to solve the moisturizing mechanism at the molecular level and the maintenance of normal condition with moisturizer, being studied with special attention to the structure of soft keratin in the corneocytes in the stratum corneum. The third subject is the so-called 500 Da rule in the penetration of drugs or cosmetics into skin, with attention paid to the disordered intercellular lipid structure in the stratum corneum.